The Mastcam‐Z Radiometric Calibration Targets on NASA's Perseverance Rover: Derived Irradiance Time‐Series, Dust Deposition, and Performance Over the First 350 Sols on Mars. Issue 12 (14th December 2022) - Merusi, M.; Kinch, K. B.; Madsen, M. B.; Bell, J. F.; Maki, J. N.; Hayes, A. G.; Joseph, J.; Johnson, J. R.; Rice, M.; Cloutis, E. A.; Applin, D.; Lemmon, M. T.; et al.
Abstract: The Mastcam‐Z radiometric calibration targets mounted on the NASA's Perseverance rover proved to be effective in the calibration of Mastcam‐Z images to reflectance (I/F) over the first 350 sols on Mars. Mastcam‐Z imaged the calibration targets regularly to perform reflectance calibration on multispectral image sets of targets on the Martian surface. For each calibration target image, mean radiance values were extracted for 41 distinct regions of the targets, including patches of color and grayscale materials. Eight strong permanent magnets, placed under the primary target, attracted magnetic dust and repelled it from central surfaces, allowing the extraction of radiance values from eight regions relatively clean from dust. These radiances were combined with reflectances obtained from laboratory measurements, a one‐term linear fit model was applied, and the slopes of the fits were retrieved as estimates of the solar irradiance and used to convert Mastcam‐Z images from radiance to reflectance. Derived irradiance time series are smoothly varying in line with expectations based on the changing Mars‐Sun distance, being only perturbed by a few significant dust events. The deposition of dust on the calibration targets was largely concentrated on the magnets, ensuring a minimal influence of dust on the calibration process. The fraction of sunlight directly hitting the calibration targets was negatively correlated with the atmospheric optical depth, as expected. Further investigation will aim at explaining the origin of a small offset observed in the fit model employed for calibration, and the causes of a yellowing effect affecting one of the calibration targets materials. Plain Language Summary: The calibration targets of Mastcam‐Z camera, mounted on the NASA's Perseverance rover, are used to calibrate Mastcam‐Z images from units of radiance to reflectance. Reflectance expresses how the sunlight is reflected by geologic targets under different geometries and wavelengths to give insights on their nature. The radiances measured within calibration targets were combined with known reflectances to obtain estimates of the local sunlight. These estimates were used to calibrate Mastcam‐Z images. Our analysis shows that the calibration targets ensured a high quality of calibration over the first 350 sols (Martian days) on Mars. The sunlight derived from the measurements can be monitored in time and shows a smooth trend with variations due to the changing distance between Mars and the Sun, and larger disturbances due to significant amounts of dust raised in the atmosphere by the wind. This dust settled on the top surface of the rover, but it minimally affected the calibration process. We also noticed that when the atmosphere is rich in dust, less sunlight can make it to the surface, and vice‐versa. More investigation will aim at explaining small variations in our calibration model and a weird effect affecting one of the materials of the calibration targets. Key Points: The Mastcam‐Z Calibration Targets ensured quality and stability in the reflectance calibration of images over the first 350 sols on Mars Dust deposited frequently on the deck of the rover and on the calibration target surfaces, especially on its permanent magnets A small offset in the fits used for calibration and a yellowing effect of one material were observed and will be further investigated